APPLICATION OF THE MAKE A MATCH METHOD TO IMPROVE MATHEMATICAL LEARNING RESULTS WITH BUILDING MATERIALS IN CLASS 3 - Setyaningrum, indah (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2019)
mathematics students expected to get understanding the concept abd traint attitude, value and skill best on the concept that has had shows execution in mathematics in the elementary school Sukamaju Baru Tapos Depok hasn’t been optimal methods theacher can use less varied it impact to mathemathics material still divicult to be understand for student and madestudent be come less active.Problems in this researth is if use make a match methods cant improve the skill of teachers students activity and the result of study on student in class 3 elemantary, school Tapos Depo?, the purpose of this research is improve the result of study on student. Percentage the result of research study of student grade 3 of the number of 41 students in cycle 1 with percentage 63%, cycle 2 inreases become 85%, Then based of these data increased by 22% each cycle so can be concleded that the make a match methods in mathematics can increased the result of study on student gard 3 elementary school Sukamaju Baru Tapos Depok. Make a match methods mathematics for used on another lessons.